Host-pathogen evolutionary signatures reveal dynamics and future invasions of vampire bat rabies - Streicker, Daniel G; Winternitz, Jamie C; Satterfield, Dara A; Condori-Condori, Rene Edgar; Broos, Alice; Tello, Carlos; Recuenco, Sergio; Velasco-Villa, Andrés; Altizer, Sonia; Valderrama, William (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Anticipating how epidemics will spread across landscapes requires understanding host dispersal events that are notoriously difficult to measure. Here, we contrast host and virus genetic signatures to resolve the spatiotemporal dynamics underlying geographic expansions of vampire bat rabies virus (VBRV) in Peru. Phylogenetic analysis revealed recent viral spread between populations that, according to extreme geographic structure in maternally inherited host mitochondrial DNA, appeared completely isolated. In contrast, greater population connectivity in biparentally inherited nuclear microsatellites explained the historical limits of invasions, suggesting that dispersing male bats spread VBRV between genetically isolated female populations. Host nuclear DNA further indicated unanticipated gene flow through the Andes mountains connecting the VBRV-free Pacific coast to the VBRV-endemic Amazon rainforest. By combining Bayesian phylogeography with landscape resistance models, we projected invasion routes through northern Peru that were validated by real-time livestock rabies mortality data. The first outbreaks of VBRV on the Pacific coast of South America could occur by June 2020, which would have serious implications for agriculture, wildlife conservation, and human health. Our results show that combining host and pathogen genetic data can identify sex biases in pathogen spatial spread, which may be a widespread but underappreciated phenomenon, and demonstrate that genetic forecasting can aid preparedness for impending viral invasions.
Keywords: zeměpis; Peru; typy dědičnosti; Inheritance Patterns; Host-Pathogen Interactions; forecasting; Geography; Microsatellite Repeats; interakce hostitele a patogenu; genom virový; Biological Evolution; zvířata; vzteklina; Rabies; spatial dynamics; roční období; virus vztekliny; Genome, Viral; Male; zoonotic disease; biologická evoluce; Seasons; Bayesova věta; mikrosatelitní repetice; Rabies virus; Animals; sex bias; mužské pohlaví; Chiroptera; Bayes Theorem; Desmodus